[Perfect hosts ; Ad Bill ; Side A Band - Lazaro, Cheche (The Probe Team, 1990)
A boatload of Vietnamese refugees seeking entry into the Philippines causes concern by temporary asylum countries over the repatrian issue. An advertising bill pending in Congress requires that all local ads be produced and acted in by Filipinos. The bill causes a debate over the practicality of the measure. A yuppie bank performing at Calesa Bar in Hyatt Regency makes waves among the young for its new sound and unorthodox way of putting music together.